Influence of construction company size on the determining factors for construction and demolition waste management - Ramos, Mário (2021)
Due to the relevance of construction and demolition waste (CDW) generation for circular economy and reduction of environmental impacts, it is important to evaluate the factors leading to constraints regarding waste. Previous researchers have assessed construction company attitudes and behaviors toward CDW management, but factors such as the presence of environmental technicians, registration of the CDW generated, commitment to the legal framework, the subcontracting regime, and construction works’ oversight were rarely addressed in terms of the differences existing within the construction sector. Thus, the objective of this research is to evaluate the relationship of these factors with construction company size. A questionnaire was sent to Portuguese construction companies, and 652 responded. The sample was divided into three groups: micro, small, and medium/large companies. Statistical data treatment was carried out to assess whether there were statistically significant differences in the mentioned factors between groups. The main conclusions highlight: the prevalence of environmental technicians working in larger companies; the registration on waste platforms being only performed consistently by medium/large companies; a considerable proportion of micro and small companies having knowledge gaps about the practices adopted; the responsibility for CDW management within the subcontracting regime being mainly from subcontractors; and the presence of a gap regarding onsite construction works oversight. These differences lead to the need to reevaluate the strategies for CDW management and adapt the strategies to the specific conditions of the construction sector, including the size of construction companies.